2004
DOI: 10.1590/s0100-83582004000100017
|View full text |Cite
|
Sign up to set email alerts
|

Weed control and green ear yield in maize

Abstract: The objective of this work was to evaluate the influence of weeding frequency on cultivar Centralmex green corn yield. Two experiments were conducted in Mossoró-RN (Brazil), with the use of sprinkler irrigation. A random block design with four replicates was used. It was observed that the total number and weight (TW) of unhusked green ears, the number and weight of marketable unhusked ears and the number and weight of marketable husked ears were reduced under no weeding treatment. The number timing of weedings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…Such reductions varied from 22% in number of marketable unhusked green ears to 58% in marketable husked green ear weight. Other authors (Silva et al, 2004b;Silva et al, 2009) also verified green ear yield reduction as a result of corn competition with weeds.…”
Section: Resultsmentioning
confidence: 75%
“…Such reductions varied from 22% in number of marketable unhusked green ears to 58% in marketable husked green ear weight. Other authors (Silva et al, 2004b;Silva et al, 2009) also verified green ear yield reduction as a result of corn competition with weeds.…”
Section: Resultsmentioning
confidence: 75%
“…Weeds have been a problem to man ever since he began cultivating crops about 10,000 BC (Silva et al, 2004). Its removal is useful because the unwanted plant compete with crops for water, soil nutrients, light and space, thus reducing crop yields (El Naim and Ahmed, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to what was observed in the present study, some authors (Silva et al, 2008) found a lack of weed control effect on total number of green ears (Table 2). However, other authors (Silva et al, 2004a) verified that total number of green ears in hoed plots was higher than in non-weeded plots, depending on the degree of interference. Such disagreement probably relates to the fact that those authors conducted three or four hoeings, which may have provided a much more effective weed control than in the present work and in other studies (Silva et al, 2008), in which only two hoeings were performed.…”
Section: Resultsmentioning
confidence: 96%
“…At those stages, corn competition with weeds for light should be higher. Be it as it may, several researchers (Gomes et al, 2007;Silva et al, 2004a) have observed reductions in corn plant height caused by weeds. Influence of corn sowing density and gliricidia intercropping ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation